BALINESE TRADITIONAL TREATMENT (BALIAN) IN PATIENTS WITH MENTAL DISORDERS - Ni Made Sri Muryani; Indah Winarni; Setyoadi (Belitung Raya Foundation, 2018)
Background: Balinese believe that mental disorders are caused after being possessed and cursed by one's ancestors, so Balinese choose traditional Balinese treatment (balian/shaman) in handling mental disorders patients. Objective: The purpose of this research is to explore deeply about the use of balian in treating patients with mental disorder. Methods: Qualitative method with an interpretive phenomenological approach was used as the research design. The research also used in-depth interview technique with semi-structured interview guidelines as a data collection strategy. The researcher conducted data analysis using Interpretative Phenomenological Analysis (IPA). Results: The research found five themes; 1) ancestors' curse, 2) possessed by a spirit, 3) believe that balian has healing power, 4) balian becomes the first choice prior to the hospital, and 5) the use of traditional and medical treatment at once. Conclusion: The result of the research showed that balian became the first choice in treating patients with mental disorders. It is because Balinese still believes that mental disorders caused by the ancestors' curse and possessed by the spirit.